Altered object exploration but not temporal order memory retrieval in an object recognition test following treatment of rats with the group II metabotropic glutamate receptor agonist LY379268 - Lins, Brittney; Ballendine, S.A.; Howland, J.G. (2014)
Temporal order memory refers to the ability to distinguish past experiences in the order that they occurred. Temporal order memory for objects is often tested in rodents using spontaneous object recognition paradigms. The circuitry mediating memory in these tests is distributed and involves ionotropic glutamate receptors in the perirhinal cortex and medial prefrontal cortex. It is unknown what role, if any, metabotropic glutamate receptors have in temporal order memory for objects. The present experiment examined the role of metabotropic glutamate receptors in temporal memory retrieval using the group II metabotropic glutamate receptor selective agonist LY379268. Rats were trained on a temporal memory test with three phases: two sample phases (60. min between them) in which rats explored two novel objects and a test phase (60. min after the second sample phase) which included a copy of each object previously encountered. Under these conditions, we confirmed that rats showed a significant exploratory preference for the object presented during the first sample phase. In a second experiment, we found that LY379268 (0.3, 1.0, or 3.0. mg/kg; i.p.; 30. min before the test phase) had no effect on temporal memory retrieval but dose-dependently reduced time spent exploring the objects. Our results show that enhancing mGluR2 activity under conditions when TM is intact does not influence memory retrieval. © 2013 Elsevier Ireland Ltd.